(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is based on a company that until now has grown rapidly due to the application of knowledge management. The company itself considers that the application of knowledge management is very important because it functions as a planned and systematic approach to ensure good application of organizational knowledge. At the same time increasing ideas, innovation, thinking, competence, and expertise. Every decision will be born with a very mature mind. Because it was decided based on various important considerations based on experience and information in terms of various important aspects. For example, knowledge management constantly studies market dynamics as well as the demands that consumers need. That way, the company always focuses on selling only what is needed by consumers or the target market. This research was conducted with a qualitative descriptive analysis, with field observations and interviews with companies. Therefore, this research aims to find out how effective is the application of knowledge management in optimizing their human capital potential?